Multi-Criteria Selection in Gram (Cicer arietinum L.) Germplasm (Global Journal of Science Frontier Research, 2023)
An experiment involving 12 genotypes of Gram Cicer arietinum L was carried out at B R D P G college farm to select varieties close to ideal plant types through a multi-criteria selection These genotypes were grown in three replications under standard package of practices to raise a good crop These genotypes were evaluated on 12 characters namely plant height days to 50 flowering primary branches plant secondary branches plant days to maturity number of pods plant number of seeds plant biological yield plant seed yield plant and the harvest index The normalized cumulative rank analysis was used to find out a preference order of these genotypes The preference order is PUSA 362 P-3719 CSG-151 E-100YM ICCI6015 GNG1581 RADHA IPC 94-94 ICC15850 ICC 3535 ICC1009 and KWR 108 The top five genotypes from these could be recommended to farmers for cultivation in this region A single table is enough to present the results of such experiments The top two varieties were compared with ideal plant type and the best one PUSA 362 could be further improved by crossing it with CSG515 IPC 94-94 ICC3535 and KWR 108
Keywords: ideotype; chickpea; cicer; normalized cumulative ranks; selection